Maintenance of Russian secondary school students’ health (organizational and administrative aspect) - V. Tretyakov, Natalia; A. Fedorov, Vladimir; V. Ketrish, Evgeniya; M. Permyakov, Oleg (International Journal of Engineering and Technology, 2018)
The relevance of the investigated problem is caused by the need to ensure the quality of educational institutions activities aimed at studentsâ€™ health maintenance through the creation of conditions for the organization and management of the activity.The purpose of the article is to develop organizational and pedagogical conditions of maintenance management process, to preserve studentsâ€™ health. Leading methodological approach to the study of this problem is systematic approach that allows considering educational organizations activities aimed at health maintenance as a certain system, to identify a specific set of its constituent elements and show their relationship. The article presents a structural-functional model of health service and according to management principles 1) covers the main areas of activity (labor division principle); 2) identifies the basis of their structural units (structuring principle); 3) the functions of health service activity as a whole, its subsidiaries and certain performers (functional operations accounting principle); 4) provides integrative management performance criteria for health service activities. The information contained in the article may be useful to teachers in terms of the organization of activity on health maintenance in educational institutions by changing organizational and management component of this activity.Â